A case of congenital rhabdomyosarcoma. Issue 5 (16th July 2019) - Wang, Senfen; Li, Ping; Li, Jianhong; Liu, Jianzhong; Jiang, Xianping; Zeng, Weibin
Abstract: A 6‐month‐old girl presented with a congenital orbital tumor diagnosed as congenital embryonal rhabdomyosarcoma. Given the location, complete surgical resection was impossible. Management with chemotherapy and proton therapy resulted in complete clearance. This case highlights the clinical and histologic features of cutaneous congenital embryonal rhabdomyosarcoma.